HLA-haplotypes and the risk of developing diabetes of type 1 diabetes in the native population of the Nenets Autonomous district - Tamara Leonidovna Kuraeva (Endocrinology Research Centre, 2017)
Nenets are Samoyedic people belonging to Ural contact minor race, with combined anthropological signs of both Caucasoid and Mongoloid races. In this population, the occurrences of type 1 diabetes mellitus (T1DM) were registered during 30 years. Aim. The study aimed to investigate the incidence of human leucocyte antigen (HLA)-haplotypes in Nenets compared with those in the Russian population. Materials and Methods. HLA-typing was performed in 61 healthy Nenets subjects residing in the Arkhangelsk district, 341 Russian subjects from Moscow and natives from the Vologda district. Results. DRB1*04-DQA1*0301-DQB1*0302 was similar in all the three study populations: 11.5%, 8.5% and 11.6% for Nenets, Moscow and Vologda populations, respectively (p > 0.05). However, the incidence of the second most important high predisposed haplotype DRB1*17(03)-DQA1*0501-DQB1*0202 was significantly lower in Nenets (1.6%) than in the Moscow and Vologda populations (10% and 7.4%, respectively) [(p1.2 = 0.03 (x2 = 4.42); p1.3 = 0.12 (x2 = 2.46)]. The incidence of DRВ1*01-DQA1*0101-DQB1*0501 haplotype specific for both Russian populations was also significantly lower in Nenets (3.3%) than in the Moscow and Vologda populations (11% and 12.4%, respectively) [(p1.2 < 0.05 (x2 = 3.34); p1.3 < 0.05 (x2 = 3.85)]. The incidence of protected haplotypes (DRB1*11-DQA1*0501-DQB1*0301 and DRB1*13-DQA1*0102-DQB1*0602/8/DRB1*13-DQA1*0103-DQB1*0602) was significantly higher in Nenets than in the Moscow and Vologda populations: 32.8% versus 12.5% and 9.1%, respectively [(p1.2 < 0.001 (x2 = 13.48); p1.3 < 0.001 (x2 = 17.3)] and 16.4% versus 8.5% and 11.1%, respectively [(p1.2 = 0.07 (x2 = 3.14); p1.3 = 0.3 (x2 = 0.97)]. The incidence of some neutral haplotypes was also significantly higher in Nenets: haplotype DRB1*12-DQA1*0501-DQB1*0301 was detected in 29.5% of Nenets compared with 2.5% and 1.2% of the Moscow and Vologda populations, respectively [(p1.2 < 0.001 (x2 = 42.43); p1.3 < 0.001 (x2 = 37.66)]; haplotype DRB1*09-DQA1*0301-DQB1*0303 was detected in 14.8% of Nenets compared with 1% and 2.5% of the Moscow and Vologda populations, respectively [(p1.2 < 0.001 (x2 = 21.9); p1.3 < 0.001 (x2 = 10.04)]. Conclusions. According to preliminary evidence, the incidence of predisposed haplotypes was significantly lower and that of protected haplotypes was significantly higher in Nenets than in the Moscow and Vologda populations, which probably play a role in the very low incidence of T1DM in Nenets.